The Pretreatment of Lignocelluloses With Green Solvent as Biorefinery Preprocess: A Minor Review - Yin, Xiaoyan; Wei, Linshan; Pan, Xueyuan; Liu, Chao; Jiang, Jianchun; Wang, Kui (Frontiers in Plant Science, 2021)
Converting agriculture and forestry lignocellulosic residues into high value-added liquid fuels (ethanol, butanol, etc.), chemicals (levulinic acid, furfural, etc.), and materials (aerogel, bioresin, etc.) via a bio-refinery process is an important way to utilize biomass energy resources. However, because of the dense and complex supermolecular structure of lignocelluloses, it is difficult for enzymes and chemical reagents to efficiently depolymerize lignocelluloses. Strikingly, the compact structure of lignocelluloses could be effectively decomposed with a proper pretreatment technology, followed by efficient separation of cellulose, hemicellulose and lignin, which improves the conversion and utilization efficiency of lignocelluloses. Based on a review of traditional pretreatment methods, this study focuses on the discussion of pretreatment process with recyclable and non-toxic/low-toxic green solvents, such as polar aprotic solvents, ionic liquids, and deep eutectic solvents, and provides an outlook of the industrial application prospects of solvent pretreatment.